Investigating Energy Justice in Demand-Side Low-Carbon Innovations in Ontario - Wyse, Susan Morrissey; Das, Runa R.; Hoicka, Christina E.; Zhao, Yuxu; McMaster, Maria-Louise (Frontiers in Sustainable Cities, 2021)
The diffusion of low-carbon innovations, including innovative products and services, is required to accelerate a low-carbon energy transition. These innovations also have the potential to alleviate and perpetuate existing social inequities, calling into question their “justness.” Energy justice is a useful analytical tool for framing justice questions related to energy. In this paper, we ask whether demand-side low-carbon energy innovations are meeting energy justice criteria. To address this question, this study develops four indicators from existing energy justice frameworks and applies them to a range of demand-side innovations offered to energy users in Ontario. The indicators are used to assess innovation availability, affordability, information, and involvement. Innovations were identified using surveys and desk research across Ontario's energy technology innovation system (ETIS). One hundred twenty-two innovations are analyzed for these four indicators, and according to intended innovation users and innovation providers. Findings suggest that three of the four indicators—availability, affordability and information are broadly being addressed, while involvement was more difficult to establish. However, the ETIS may be perpetuating inequities through an over emphasis of innovations for particular energy users, such as private businesses, alongside under-emphasis on potentially marginalized actors, such as low-income households and renters. Furthermore, government-delivered, publicly owned or regulated innovation providers place a greater emphasis on energy justice, including the provision of innovations for marginalized actors. This study aids our understanding of energy justice in low-carbon energy innovations and is critical given that in the context of funding cuts to public services, there may be an increased reliance on decentralized actors. The consideration of justice gaps that emerge through such decentralization should not be overlooked. Our findings suggest that within Ontario's ETIS, who provides innovations matters. Given the insights presented in this study, this research approach and the developed indicators could be applied to other contexts and socio-technical systems. The application of energy justice indicators, derived from existing scholarship, therefore presents an important opportunity to address current and understudied practical energy challenges.